The Role of Stoicism in “Robinson Crusoe” By Daniel Defoe (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the issue of human nature in different political stages in Robinson Crusoe with some comparative examples from Gulliver’s Travels. Hobbes and Locke, the seventeenth century philosophers, are known for their political philosophies on human nature and the development of social societies and governments by this. These features can be seen in Daniel Defoe’s Robinson Crusoe clearly and they can be scrutinized in this respect, for Defoe’s views on human nature are similar to these two philosophers ‘thoughts. We can recognize the individualism, stoicism and egocentricity in Robinson Crusoe’s character, and his fears and doubts that depict human nature perfectly.